Recovery of kidney function after AKI because of COVID‐19 in kidney transplant recipients. (29th June 2021) - Bajpai, Divya; Deb, Satarupa; Bose, Sreyashi; Gandhi, Chintan; Modi, Tulsi; Katyal, Abhinav; Saxena, Nikhil; Patil, Ankita; Thakare, Sayali; Pajai, Atim E.; Haridas, Ashwathy; Keskar, Vaibhav S.; et al.
Summary: Evidence on the evolution of graft function in kidney transplant recipients recovering from coronavirus disease‐2019 (COVID‐19) is lacking. This multicenter observational study evaluated the short‐term clinical outcomes in recipients with acute kidney injury (AKI) secondary to COVID‐19. Out of 452 recipients following up at five centers, 50 had AKI secondary to COVID‐19. 42 recipients with at least 3‐month follow‐up were included. Median follow‐up was 5.23 months [IQR 4.09–6.99]. Severe COVID‐19 was seen in 21 (50%), and 12 (28.6%) had KDIGO stage 3 AKI. Complete recovery of graft function at 3 months was seen in 17 (40.5%) patients. Worsening of proteinuria was seen in 15 (37.5%) patients, and 4 (9.5%) patients had new onset proteinuria. Graft failure was seen in 6 (14.3%) patients. Kidney biopsy revealed acute tubular injury (9/11 patients), thrombotic microangiopathy (2/11), acute cellular rejection (2/11), and chronic active antibody‐mediated rejection (3/11). Patients with incomplete recovery were likely to have lower eGFR and proteinuria at baseline, historical allograft rejection, higher admission SOFA score, orthostatic hypotension, and KDIGO stage 3 AKI. Baseline proteinuria and the presence of orthostatic hypotension independently predicted incomplete graft recovery. This shows that graft recovery may remain incomplete after AKI secondary to COVID‐19.